DIPG-36. CLINICAL, RADIOLOGICAL, AND HISTO-MOLECULAR CHARACTERISTICS OF DIFFUSE INTRINSIC PONTINE GLIOMA IN PATIENTS WHO SURVIVE LESS THAN 3 MONTHS FROM DIAGNOSIS: A REPORT FROM THE INTERNATIONAL DIPG REGISTRY. (23rd April 2019) - Dahl, Nathan; Lane, Adam; Bandopadhayay, Pratiti; Minturn, Jane; Dodgshun, Andrew; Parkin, Sara; Shih, Chie-Schin; Hassall, Tim; Hansford, Jordan; Samson, Yvan; Cai, LinBo; Leary, Sarah; et al.
Abstract: Diffuse intrinsic pontine glioma (DIPG) is aggressive brainstem tumor with median survival of < 1 year. We queried data from the International DIPG Registry to define clinical, radiological, histological, and molecular characteristics of DIPG patients who survived < 3 months from diagnosis. Among 909 patients enrolled on the registry, 59 (6.5%) had overall survival (OS) of < 3 months. Median age at diagnosis was 5.8 years (range 0–13 years), and 12 (20%) were age < 3 years at diagnosis. Most presented with short duration of symptoms (< 6 weeks, 50/58; 86%) and at least one cranial nerve palsy, cerebellar sign, and/or pyramidal tract sign (52/54; 96%). Twenty-two (41%) presented with hydrocephalus, including 10 who required CSF diversion. All had extra-pontine extension on diagnostic imaging. Less than half of patients (25/56, 45%) received therapy; of these, 11 received radiation (RT) only, 12 received RT and chemotherapy, and 2 received chemotherapy only. Most received steroids (48/52; 92%), including 27 who received palliative steroids at the end of life. Biopsy and autopsy were performed in 11/57 (19%) and 13/58 (22%) cases, respectively. Of 22 for whom histology was known, 19 represented high-grade glioma subtypes, 2 low-grade gliomas, and 1 embryonal tumor. Six were molecularly characterized, and 3 harbored H3K27M mutations. Ongoing work will aim to further characterize the molecular features of these tumors with exceptional poor outcomes despite therapy.